(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2024)
The article focuses on the impact of temperature on the reliability of electronic components, as in non-redundant radio-electronic equipment, the failure of any component typically leads to the failure of the entire device. The methods and approaches used to analyze the electronics reliability, predict operational lifespans, and to enhance it are considered. Thermal effects are among the most significant factors influencing reliability indicators of electronics, such as the probability of failure-free operation and mean time to failure. The sequence of accounting for thermal factors during the calculations of operational failure rate, mean time to failure, and the probability of failure-free operation according to the recommendations of Ukrainian State Standards is analyzed. The primary focus is on calculating the mean time to failure for various groups of resistors, capacitors, integrated circuits, and semiconductor components. Modern approaches to reliability assessment are used in the study, particularly a combination of failure physics and computer modeling. It was determined that the difference in the mean time to failure between the most and least thermally resilient electronic components of radio-electronic equipment can be very significant and only increases with rising temperatures.